(untitled) (Research, Society and Development, 2020)
Plants are considered a rich source of bioactive compounds and an alternative agent for insect control. Among them, representatives of the Lamiaceae family are the best known for this potential, as they produce volatile compounds with insecticidal activities, known as essential oils, as is the case with Ocimum gratissimum. In this way, the present work had as objective, to determine the chemical composition of the oil of the leaves of O. gratissimum and its potential insecticide against the cockroach Nauphoeta cinerea. For that, the essential oil was chemically characterized by means of a Gas Chromatograph coupled to a Mass Spectrometer (GC/MS). As for the insecticidal action, nymphs (20 days of age) were used and the fumigation methodology was used in concentrations ranging from 50 to 1000 μg of oil per mL of air. Mortality rates were observed every 12 hours for 1 day. The results showed that the essential oil has insecticidal properties, since it had a median lethal concentration (LC50) of 516 µg/mL. Such property may be related to the heterogeneous composition of the oil, which had 12 terpenic compounds, with 1.8 Cineole being the major compound (30.04%). Thus, the essential oil of O. gratissimum has an insecticidal activity and can be used to fight pests, as in the case of cockroaches.